Readiness of Junior High School Students to Follow Natural Science Learning by Using Cooperative Learning Model - Rahman Rahman (Universitas Muhammadiyah Makassar, 2021)
The implementation of education in schools that involve educators is one of the determinants of the success of education through its performance at the institutional and instructional levels. This study aims to determine the readiness of the students of SMP Negeri 2 Maros in learning natural sciences using the cooperative learning model. The design used in this study was a qualitative case study. The selection of cases in this study was based on the consideration of educators on the grounds that there were 6 students of class VIII H who had good potential and achievements. The data were collected through observation, depth interviews, and documentation. The results showed that there was only one out of six students who was declared unprepared in cooperative learning. That student does not meet the criteria or indicators of cooperative learning with the information that students prefer to study alone in a calm and not crowded atmosphere. The rest, they are ready to take part in cooperative learning that requires cooperation with one another. Based on the results of the study, it can be concluded that the majority of students in class VIII H of SMP Negeri 2 Maros stated that they were ready to take part in learning with a cooperative learning model in the subjects of natural sciences.